Comparative Efficacy Of Triple Therapy And Sequential Therapy In Helicobacter Pylori Eradication: A Randomized Controlled Trial (Journal of Pharmaceutical Negative Results, 2024)
Background: Helicobacter pylori is identified to be a cause of several diseases associated with the GI tract including gastritis,ulcer and gastric cancer. In Pakistan, you find that 81 percent of adult population has been infected by this type of disease. Theemergence of resistance to antibiotics has reduced the efficacy of the conventional triple therapy; it has become necessary toevaluate other new chewing regimens like sequential therapy which appear superior in this regard in terms of eradication.Objectives: To compare the outcome of conventional triple therapy with that of sequential therapy in the eradication ofHelicobacter pylori in infected local population.Study Design: A randomized controlled trialPlace and Duration of Study: The study was conducted at the Department of Gastroenterolgy, ward and OPD, Lady ReadingHospital (LRH), Peshawar, Pakistan. The duration of the study was six months, from 16th September 2021 to 24th March 2022.Methods: This study was a randomized controlled trial was conducted at Gastroenterolgy ward and OPD, Department ofGastroenterolgy, LRH Peshawar. In each group there were two arms, one of which included 326 patients in total. The therapiesoffered to the patients were evaluated using consecutively collected samples and compared statistically. The duration adopted inthe study of the eradication rates among the patients was six months counting from the treatment period.Results: The age of the patients was mean of 38.5 ± 11.59 and male to female ration was estimated as 0.55 each. Sequential therapyyielded a significantly higher eradication rate than triple therapy: p = 0.04.Conclusions: Closely, there was also better evidence of tolerability when compared to triple therapy regardless of grade offavourable eradication and fewer side effects which was significant at p< 0.05. It is time that the solution of the sequentialtherapy strategy as the first choice of treatment should be produced, in order to improve the condition of the patient, and to preventthe interruption of the cyclic antibiotic resistance.